A multi-pass small deformation drawing process for making high strength steel wire

CN122722682BActive Publication Date: 2026-11-03NINGXIA ZHONGNENG HENGLI STEEL WIRE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611184061.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-11-03
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

现有钢丝拉拔工艺中塑性随变形累积而持续耗竭,成品断后伸长率较低。

Method used

A multi-pass small deformation drawing process is adopted, with each drawing section consisting of 2 to 3 drawing sections. Adjacent drawing sections undergo sorbitization treatment and nano-lubricating film recoating to form a uniform double-layer solid lubricating film. The single-pass compression ratio is controlled between 8 and 26%, and drawing is performed using a drawing die with a gradually tapered angle design.

Benefits of technology

It effectively eliminates dislocation entanglement and lattice distortion caused by work hardening, restores plasticity reserves, reduces surface scratches and friction damage during drawing, and improves the surface quality and strength-toughness balance of steel wire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The application discloses a multi-pass small deformation drawing process for preparing high-strength steel wires, which comprises 2-3 drawing sections, and the following processes are sequentially performed between adjacent drawing sections: the steel wire is heated to 880-950 DEG C for austenitizing, then is isothermally transformed into sorbite at 450-550 DEG C, and is cooled to below 200 DEG C under a protective atmosphere; then the surface of the steel wire is recoated with a primer and coated with a working film to form a double-layer solid lubricating film. The process of the application restores the plastic storage of the steel wire through inter-section sorbitizing treatment, and the inter-section primer recoating reconstructs the chemical bonding lubricating film, which forms a closed-loop cooperation of drawing, sorbitizing and re-lubricating with the drawing section, and effectively solves the technical problems of continuous depletion of plasticity with deformation accumulation and low breaking elongation of the finished product in the existing steel wire drawing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of metal wire processing technology, and more specifically, relates to a multi-pass small deformation drawing process for preparing high-strength steel wire. Background Technology

[0002] High-strength steel wire is the basic material for high-end products such as steel wire rope, steel cord, and springs. Industrially, it is mainly produced through a cold drawing process: the wire rod is passed through drawing dies with decreasing apertures in sequence, and plastic deformation occurs at room temperature, causing the grains to elongate and the dislocation density to increase sharply, thereby obtaining high strength.

[0003] Traditional steel wire drawing processes mainly employ continuous multi-pass drawing, where all deformation is accumulated during a single wire threading process, and uniform heat treatment is performed only after drawing is complete. For example, CN113680840A discloses a drawing process for high-carbon steel fine wire, in which high-carbon pearlitic steel wire with a diameter not exceeding 0.65mm is continuously cold-drawn to the finished product through multiple drawing dies, with a deformation of 6-20% per pass. The entire process is continuous drawing without intermediate annealing, meaning that all deformation is accumulated during a single wire threading process.

[0004] However, during multiple consecutive drawing passes, the continuous accumulation of deformation leads to the continuous accumulation of dislocation entanglement and lattice distortion, while forming irreversible microscopic damage such as microcracks and local necking tendency. The plastic reserve is gradually depleted, and the elongation after fracture of the finished product is generally low, making it difficult to meet the requirements of high-end steel wire ropes for elongation after fracture. Summary of the Invention

[0005] The technical problem to be solved by this application is that in the existing steel wire drawing process, the plasticity is continuously depleted as deformation accumulates, resulting in a low elongation after fracture of the finished product.

[0006] To address the aforementioned technical problems, this application provides a multi-pass, small-deformation drawing process for preparing high-strength steel wire, comprising 2-3 drawing sections, each of which performs multiple drawing passes on the steel wire, with the following steps sequentially executed between adjacent drawing sections: The steel wire is heated to 880-950℃ to austenitize it, and then isothermal transformation is carried out at 450-550℃ to transform the supercooled austenite into sorbite. Finally, it is cooled to below 200℃ under a protective atmosphere. After sorbitizing, a base film is recoated onto the surface of the steel wire, and then a working film is coated on the base film to form a uniform double-layer solid lubricating film.

[0007] As a preferred option, each drawing section includes 3 to 4 consecutive drawing passes, and the total compression ratio of each drawing section does not exceed 55%.

[0008] Furthermore, the single-pass compression ratio within each drawing section is 8–26%, preferably 16–23%.

[0009] Furthermore, the working film is formed by coating with a nano-modified lubricant containing 1–3 wt% hexagonal boron nitride (h-BN) nanoparticles.

[0010] As a preferred option, in the multi-pass drawing process, the cone angle of the compression zone of the drawing die gradually decreases from the inlet end to the outlet end.

[0011] Furthermore, the inlet cone angle of the compression zone of the drawing die is 12-15°, and the outlet cone angle of the compression zone is 6-8°.

[0012] As a preferred option, the isothermal transformation is a salt bath isothermal transformation; the salt bath isothermal transformation includes: The austenitized steel wire is immersed in a molten salt bath containing nitrates at a temperature of 450–550°C for 10–60 seconds.

[0013] As a preferred option, the protective atmosphere is nitrogen or a mixture of nitrogen and propane.

[0014] As a preferred option, the base film recoating includes: The surface of the cooled steel wire is steam-treated or sprayed with deionized water to regenerate hydroxyl groups on the surface of the steel wire. A dipping solution is applied to the cooled steel wire surface, and then dried and cured at 120-150℃ for 30-60 seconds to form a nano pre-coated base film; the dipping solution is prepared by a silane coupling agent and 1-3 wt% nano hexagonal boron nitride particles.

[0015] Furthermore, prior to the first drawing section, the following is also included: The wire rod is dip-coated with the aforementioned dip-coating solution, and then dried and cured at 120–150°C for 60–90 seconds to form a nano-pre-coated base film on the surface of the wire rod.

[0016] The beneficial effects of this application are as follows: This application employs inter-segment sorbitization treatment, ensuring that the steel wire undergoes a microstructure transformation and refinement from austenitization to isothermal sorbitization after each stage of drawing. This effectively eliminates dislocation entanglements and lattice distortion caused by work hardening, re-acquires a fine lamellar sorbitic structure, and restores plasticity reserves. Two to three cycles ensure that plasticity does not accumulate and deplete throughout the entire drawing process. Simultaneously, the double-layer solid lubricating film formed by inter-segment base film recoating and working film reconstruction reduces surface scratches and frictional damage during drawing, improving the surface quality of the steel wire. Controlled inter-segment austenitization temperature and holding time prevent grain coarsening, ensuring a balance between the strength and toughness of the steel wire. Detailed Implementation

[0017] The embodiments of the technical solution of this application will be described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.

[0018] This application provides a multi-pass, small-deformation drawing process for preparing high-strength steel wire, comprising 2 to 3 drawing stages, each drawing stage performing multiple drawing passes on the steel wire, and the following steps being performed sequentially between adjacent drawing stages: The steel wire is heated to 880-950℃ to austenitize it, and then isothermal transformation is carried out at 450-550℃ to transform the supercooled austenite into sorbite. Finally, it is cooled to below 200℃ under a protective atmosphere. After sorbitizing, a base film is recoated onto the surface of the steel wire, and then a working film is coated on the base film to form a uniform double-layer solid lubricating film.

[0019] In this application, a "drawing section" refers to a unit within a continuous drawing process, with each drawing section comprising multiple consecutive passes. The connection between two adjacent drawing sections is not a simple sequential sequence, but rather incorporates two process segments: a "sorbitizing treatment section" and a "nano-lubricant recoating section." Together with the drawing sections, these form a cyclical unit structure of "drawing, sorbitizing treatment, nano-lubricant recoating, and the next drawing section." The entire process comprises 2 to 3 such cyclical units, meaning it is executed 2 to 3 times.

[0020] The mechanism of sorbitization is as follows: After 3-4 passes of cold drawing, the steel wire's microstructure is work-hardened deformed pearlite, containing high-density dislocations and lattice distortion, resulting in a significant decrease in plasticity reserves. Inter-pass sorbitization first heats the steel wire to the austenitizing temperature range of 880-950℃, completely transforming the deformed pearlite into austenite. Then, the austenitized wire is rapidly placed in an isothermal transformation medium at 450-550℃, where the supercooled austenite undergoes an isothermal pearlite transformation, forming fine lamellar sorbite. This fine lamellar sorbite possesses both high strength and excellent cold-working plasticity, allowing it to withstand large deformations, thus restoring the steel wire's plasticity reserves and enabling the next drawing pass to begin with a favorable microstructure.

[0021] The mechanism of inter-section base film recoating and working film coating is as follows: During the sorbitizing process, the austenitizing heating causes the organic components of the previous stage's lubricating film to completely decompose and burn away. Therefore, after sorbitizing, the steel wire surface is either bare steel or only has residual carbides. After cooling to below 200°C in a protective atmosphere, a base film is first recoated onto the steel wire surface, and then a working film is coated on top of the base film, reforming a double-layer solid lubricating film of base film and working film. The base film provides a chemical anchoring foundation for the working film, while the working film bears the main friction-reducing function. The double-layer structure ensures sufficient surface lubrication protection for the next stage of drawing, starting from the optimal surface condition.

[0022] Sorbiticization restores the fine lamellar sorbite structure, creating favorable microstructural conditions for the next stage of drawing; the reconstruction of the inter-stage double-layer lubricating film creates favorable surface conditions for the next stage of drawing; the next stage of drawing starts from the dual beneficial state of microstructural restoration and good surface lubrication, the deformation process is more uniform and gentle, the degree of work hardening is relatively light, and the subsequent sorbiticization treatment makes it easier to achieve microstructural restoration.

[0023] In one implementation, each drawing segment includes 3 to 4 consecutive drawing passes, and the total compression ratio of each drawing segment does not exceed 55%.

[0024] Specifically, three passes per segment are preferred, while four passes are suitable for steel grades with larger diameters or greater deformation resistance. With fewer than three passes, the single-pass compression ratio is too high, losing the advantage of small deformation; with more than four passes, the total compression ratio of a single segment may exceed the 55% upper limit. When the total segment compression ratio exceeds 55%, the degree of work hardening increases sharply, the dislocation density increases significantly, and even subsequent sorbitization treatment cannot fully restore the plasticity reserve, significantly increasing the risk of wire breakage and decreasing process stability. Optionally, the single-pass compression ratio within each drawing segment is 8–26%, preferably 16–23%. In this application, the compression ratio of each pass refers to the cross-sectional area compression ratio; the total segment compression ratio of the drawing segment is the cumulative value of the compression ratios of all passes in that segment, i.e. .

[0025] in, This represents the compression rate for each pass.

[0026] In one implementation, the working film is formed by coating a nano-modified lubricant containing 1–3 wt% hexagonal boron nitride (h-BN) nanoparticles.

[0027] Specifically, h-BN has a hexagonal layered crystal structure similar to graphite, with BN atoms within the layers bonded by strong covalent bonds and between the layers by weak van der Waals forces. Under drawing shear force, slippage occurs between the h-BN layers, acting as a solid lubricant. Simultaneously, h-BN has a high in-plane thermal conductivity; adding it to a lubricant can locally improve thermal conductivity in the deformation zone, helping to reduce the drawing temperature rise.

[0028] In one implementation, during the multi-pass drawing process, the cone angle of the compression zone of the drawing die gradually decreases from the inlet end to the outlet end.

[0029] Preferably, the inlet cone angle of the compression zone of the drawing die is 12-15°, and the outlet cone angle of the compression zone is 6-8°.

[0030] Specifically, a larger cone angle is used at the inlet end, which generates a greater wedging effect when the steel wire just enters the compression zone. This facilitates the introduction and uniform distribution of the nano-lubricant between the steel wire and the die interface. Subsequently, the cone angle decreases linearly along the compression zone, reaching a smaller cone angle at the outlet end. This reduces the deformation rate at the end, ensuring the accuracy of the wire diameter and the surface finish. This gradual design avoids the contradiction between insufficient lubrication at the inlet and scratches on the outlet surface of traditional fixed-cone-angle dies.

[0031] In one implementation, the isothermal transformation is a salt bath isothermal transformation; the salt bath isothermal transformation includes immersing the austenitized steel wire in a nitrate mixed molten salt bath at a temperature of 450-550°C for 10-60 seconds.

[0032] Nitrate-mixed molten salt exhibits good fluidity, high heat transfer coefficient, and stable chemical properties within this temperature range, making it a mature industrial isothermal quenching medium. An immersion time of 10–60 seconds is sufficient for fine-gauge steel wires to complete the isothermal transformation from supercooled austenite to sorbite. The finer the steel wire, the shorter the required immersion time. Exemplarily, the nitrate-mixed molten salt bath is prepared from sodium nitrate (NaNO3) and potassium nitrate (KNO3) at a mass ratio of 40:60 to 60:40, preferably 50:50. In one implementation, the protective atmosphere is nitrogen or a mixture of nitrogen and propane. Using nitrogen protection (purity ≥99.0%) effectively isolates the steel wire from air, preventing oxidation of the wire surface in the austenitizing heating section at 880–950℃ and the cooling section after the isothermal transformation in the salt bath at 450–550℃. A mixture of nitrogen and a small amount of propane is preferred. By controlling the proportion of propane, the carbon potential in the furnace is kept slightly lower than the carbon content of the steel wire (e.g., 0.7-0.9%C), which prevents decarburization and avoids carbon increase.

[0033] In one implementation, the base film recoating includes: steam treatment or spraying deionized water on the cooled steel wire surface to regenerate hydroxyl groups on the steel wire surface; coating the cooled steel wire surface with an impregnation solution, and drying and curing at 120-150°C for 30-60 seconds to form a nano pre-coated base film; the impregnation solution is prepared by a silane coupling agent and 1-3 wt% nano hexagonal boron nitride particles.

[0034] Specifically, after the steel wire undergoes sorbitization treatment, the original organic lubricating film on its surface (including the initial pre-coated base film) is burned away by high temperature. After cooling to below 200°C under a protective atmosphere, the steel wire surface is in a clean, bare steel state. First, a brief steam treatment or deionized water spraying is applied to allow water molecules to adsorb and dissociate on the steel surface, generating hydroxyl groups (-OH), providing chemical bonding sites for the silane coupling agent. Subsequently, a silane coupling agent and h-BN dip-coating solution are applied. The alkoxy groups of the silane coupling agent hydrolyze to generate silanols (Si-OH), which condense with the hydroxyl groups on the steel surface to form Si-O-Fe covalent bonds. Simultaneously, intermolecular silane polymerization forms a siloxane network, anchoring the h-BN nanoparticles within this network. Drying and curing at 120–150°C accelerates the condensation reaction, and the base film cures in 30–60 seconds. The recoated base film forms a chemical bond with the steel substrate, providing a strong anchoring foundation for the subsequent working film coating. Preferably, the silane coupling agent is an epoxy-containing silane coupling agent, such as KH-560.

[0035] In one implementation, before the first drawing section, the process further includes: applying the dip coating solution to the wire rod, and then drying and curing the wire rod at 120–150°C for 60–90 seconds to form a nano-pre-coated substrate film on the surface of the wire rod.

[0036] Specifically, a nano-pre-coated substrate film before the first drawing stage replaces the traditional phosphating and saponification pretreatment; the chemical bonding (Si-O-Fe) between the silane coupling agent and the wire rod surface replaces the physical adhesion of the phosphating film; and the solid lubrication function of h-BN replaces the lubrication carrier function of the saponification powder. The chemical bonding mechanism of the pre-coated substrate film is the same as that of the inter-stage substrate film recoating mentioned above. However, because the wire rod diameter is larger and this is the first coating, the drying and curing time is appropriately extended to 60-90 seconds to ensure complete curing.

[0037] The present application is further illustrated below through examples and comparative examples. Unless otherwise specified, the raw materials used in the examples and comparative examples are all from the same batch of 82B high-carbon steel wire (chemical composition: C 0.82%, Si 0.25%, Mn 0.75%, diameter 4.0 mm), and the target finished wire diameter is 1.45 mm. The process parameters and wire performance test results for each example and comparative example are summarized in Tables 1 and 2.

[0038] Example 1 This embodiment includes 3 drawing sections, each with 3 passes, for a total of 9 passes, to draw the Φ4.00mm raw steel wire to the Φ1.45mm finished product.

[0039] (1) Initial nano pre-coating: The raw steel wire is dipped in a coating solution, which is prepared by silane coupling agent KH-560 and 2wt% nano h-BN particles (particle size 100-500nm); after dipping, it is dried and cured at 150℃ for 60s to form a nano pre-coating base film on the surface of the steel wire.

[0040] (2) Segmented drawing: The partial compression ratio and die exit diameter design values ​​for each pass of the three drawing segments are as follows: The inlet diameter of the first drawing section is 4.00 mm. The partial compression rates of the first to third passes are 19.90%, 22.09%, and 21.49%, respectively, with corresponding outlet diameters of 3.58 mm, 3.16 mm, and 2.80 mm. The total compression rate of the section is approximately 51.0%. The inlet diameter of the second drawing section is 2.80 mm. The partial compression rates of the first to third passes are 20.92%, 20.51%, and 19.65% respectively, with corresponding outlet diameters of 2.49 mm, 2.22 mm, and 1.99 mm. The total compression rate of the section is approximately 49.5%. The inlet diameter of the third drawing section is 1.99 mm. The partial compression rates of the first to third passes are 19.99%, 18.19%, and 18.89% respectively, and the corresponding outlet diameters are 1.78 mm, 1.61 mm, and 1.45 mm respectively. The total compression rate of the section is approximately 46.9%.

[0041] All nine passes used a drawing die with a compression zone cone angle decreasing from 14° at the inlet to 7° at the outlet. The concentration of h-BN in the nano-modified lubricant used was 2wt%, and the drawing speed was 4.0 m / s. During the drawing process, the wire temperature at the die outlet was monitored online by an infrared thermometer and kept below 200°C throughout to avoid thermal degradation of the lubricating film.

[0042] (3) Inter-stage sorbitization treatment: It is performed once between the first drawing section and the second drawing section, and once between the second drawing section and the third drawing section. In both cases, medium-frequency induction heating is used to complete the austenitization. Then, it is immersed in a molten salt bath of nitrate mixed with sodium nitrate and potassium nitrate at a mass ratio of 50:50 for isothermal transformation. After the isothermal transformation is completed, it is desalted and dried, and then cooled to 150°C in a protective atmosphere of N2 and C3H8 (N2≥99.0%+C3H8 0.5~1.0%).

[0043] The treatment after the first drawing stage involves an induction frequency of 3kHz, heating to 910℃, holding at a mixed protective atmosphere for 10s, a salt bath temperature of 500℃, and immersion for 30s; the treatment after the second drawing stage involves an induction frequency of 5kHz, heating to 900℃, holding at a temperature of 8s, a salt bath temperature of 500℃, and immersion for 20s.

[0044] (4) Inter-section base film recoating and working film coating: After two sorbitizing treatments, the following same procedure is followed: The cooled steel wire is first steam-treated for 2s to regenerate hydroxyl groups on the surface; then the dipping solution described in step (1) is sprayed on, and dried and cured at 150°C for 45s to form a base film; then a nano-modified lubricant containing 2wt% h-BN is sprayed on the base film to form a working film. The base film and the working film constitute a double-layer solid lubricating film.

[0045] After the third drawing stage is completed, a Φ1.45mm finished steel wire is obtained directly without further sorbitizing treatment and lubricating film coating.

[0046] Example 2 The process steps are basically the same as in Example 1, with the main difference being: In the sorbitizing treatment after the first drawing stage, the austenitizing temperature is 880℃, and the holding time is 15s; the isothermal transformation temperature is 550℃, and the impregnation time is 20s. In the sorbitizing treatment after the second drawing stage, the austenitizing temperature is 880℃, and the holding time is 12s; the isothermal transformation temperature is 550℃, and the immersion time is 15s.

[0047] The remaining parameters are the same as in Example 1.

[0048] Example 3 The process steps are basically the same as in Example 1, with the main difference being: In the sorbitizing treatment after the first drawing stage, the austenitizing temperature is 950℃, and the holding time is 8s; the isothermal transformation temperature is 450℃, and the impregnation time is 50s. In the sorbitizing treatment after the second drawing stage, the austenitizing temperature is 950℃, and the holding time is 6s; the isothermal transformation temperature is 450℃, and the immersion time is 35s.

[0049] The remaining parameters are the same as in Example 1.

[0050] Example 4 The process steps are basically the same as in Example 1, the main difference being that the third drawing stage uses 4 drawing passes, for a total of 10 passes.

[0051] The inlet diameter of the first drawing section is 4.00 mm. The partial compression rates of the three passes are 18.10%, 20.39%, and 19.94% respectively, corresponding to outlet diameters of 3.62 mm, 3.23 mm, and 2.89 mm respectively. The total compression rate of the section is approximately 47.8%. The inlet diameter of the second drawing section is 2.89 mm, and the partial compression rates of the three passes are 19.68%, 18.37%, and 18.69% respectively, corresponding to outlet diameters of 2.59 mm, 2.34 mm, and 2.11 mm respectively, with a total section compression rate of approximately 46.7%. The inlet diameter of the third drawing section is 2.11 mm. The partial compression rates of the four passes are 18.06%, 17.01%, 16.50%, and 16.83% respectively, and the corresponding outlet diameters are 1.91 mm, 1.74 mm, 1.59 mm, and 1.45 mm respectively. The total compression rate of the section is approximately 52.8%.

[0052] The remaining parameters are the same as in Example 1.

[0053] Comparative Example 1 The process steps are basically the same as in Example 1, the main difference being that the austenitizing temperature of each stage of the sorbitizing treatment is 850℃, and the holding time is extended to 20s. The other parameters are the same as in Example 1.

[0054] Comparative Example 2 The process steps are basically the same as in Example 1, with the main difference being that the isothermal transformation temperature of each stage of the sorbitization treatment is 580℃, and the salt bath immersion time is maintained at 30s. The remaining parameters are the same as in Example 1.

[0055] Comparative Example 3 Using traditional continuous drawing process: The same 82B high-carbon steel wire as in Example 1 was used. After traditional pickling, phosphating and saponification pretreatment, without nano pre-coating treatment, it was continuously drawn to a finished product of Φ1.45mm. The entire line was continuously drawn without any heat treatment or re-lubrication in between.

[0056] The compression rates for each pass were 22.12%, 20.88%, 19.91%, 18.94%, 18.07%, 16.70%, 16.48%, 15.09%, 14.23%, 13.04%, and 9.00%, respectively, and the exit diameters for each pass were 3.53mm, 3.14mm, 2.81mm, 2.53mm, 2.29mm, 2.09mm, 1.91mm, 1.76mm, 1.63mm, 1.52mm, and 1.45mm, respectively.

[0057] Since plasticity is continuously depleted as deformation accumulates, the compression ratio of each pass must decrease monotonically along the drawing direction. Therefore, the number of passes required to achieve the same final diameter increases from 9 passes in Example 1 to 11 passes.

[0058] Comparative Example 4 The process steps are basically the same as in Example 1, with the main difference being: After inter-segment sorbitization treatment, the base film recoating step is eliminated. That is, after the steel wire is cooled to 150°C in a protective atmosphere, a nano-modified lubricant containing 2wt%h-BN is directly sprayed to form a working film.

[0059] The remaining parameters are the same as in Example 1.

[0060] Comparative Example 5 The process steps are basically the same as in Example 1, with the main difference being: No sorbitization treatment is performed between stages. That is, after the first drawing stage is completed, the steel wire is not heated and isothermal transformed. Instead, the base film is recoated and the working film is coated directly at room temperature before the second drawing stage is carried out.

[0061] The remaining parameters are the same as in Example 1.

[0062] The process parameters for Examples 1-4 and Comparative Examples 1-5 are detailed in Table 1 below.

[0063] Table 1 Summary of process parameters

[0064] Note: ① In the table, "x / y / z" correspond to the parameter values ​​of the first / second / third paragraphs, respectively.

[0065] The steel wires obtained in Examples 1-4 and Comparative Examples 1-5 were subjected to the following performance tests. For each group of steel wires, n=10 samples were randomly cut, and the average value was taken: (1) Tensile strength and elongation after fracture: conducted according to GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Test method at room temperature"; (2) Number of 360° torsion cycles: Performed according to GB / T 239.1-2023 "Metallic Materials Wire - Part 1: Unidirectional Torsion Test Method", and record the number of torsion cycles before the specimen breaks; (3) Number of 180° bends: The test shall be conducted in accordance with GB / T 238-2013 "Metallic Materials Wires Repeated Bending Test Method", and the number of bends before the specimen breaks shall be recorded; (4) Surface quality: Visually inspect the surface condition and defects of the steel wire under natural light or equivalent artificial lighting. Evaluate according to the following four levels: a) Smooth and free of visible defects: The surface is bright and smooth, without any visible cracks, folds, scars, scratches, pits, rust, or oxide scale. b) Minor scratches: The surface is shiny, but there are minor longitudinal scratches that are visible to the naked eye. The depth of these scratches does not exceed half of the wire diameter tolerance, and the number of scratches per meter does not exceed 3. c) Obvious scratches: There are easily visible scratches or local pits on the surface, the depth of the scratches exceeds half of the diameter tolerance of the steel wire, or the number of scratches per meter exceeds 3. d) Rough surface: The surface is continuously pitted, rough and dull, or has defects such as rust, oxide scale, and folds, which have an adverse effect on the performance of the steel wire. (5) Decarburization layer depth: The metallographic method of GB / T 224-2019 "Determination of Decarburization Layer Depth of Steel" was used to determine the maximum total decarburization layer depth on the surface of the steel wire. The magnification of the measurement was 100, and the average value of 5 measurements was taken as the total decarburization layer depth of the sample. (6) Average grain size: The average grain size of metals is determined by the intercept method in GB / T 6394-2017 "Method for determination of average grain size of metals". The measurement magnification is 200, and 5 fields of view are observed. The average value is taken as the final result.

[0066] Table 2. Test Results of Steel Wire Properties

[0067] Results analysis: Examples 1 to 4 were all carried out within the process parameters defined in this application. The elongation after fracture of Examples 1 to 4 were 12.6%, 10.9%, 11.3%, and 13.1%, respectively, all higher than 5.2% of Comparative Example 3 and 7.1% of Comparative Example 5. The 360° torsion cycles were 42, 38, 36, and 44 times, respectively, and the 180° bending cycles were 30, 27, 25, and 32 times, respectively. The visual appearance of all examples was smooth with no visible defects. In terms of all measured plasticity indicators and surface quality, Examples 1 to 4 were significantly better than the comparative examples.

[0068] The austenitizing temperature of Example 1 is 910℃ / 900℃, which allows cementite to fully dissolve into austenite and results in a uniform carbon concentration. The isothermal transformation temperature of 500℃ is in the middle of the range of 450-550℃, with moderate supercooling, and the overall mechanical properties are superior to those of other examples.

[0069] In Example 2, the austenitizing temperature of 880°C is at the lower limit specified in this application. At this temperature, the driving force for cementite dissolution is weaker than at 910°C, and the carbon concentration in the austenite may not be completely homogenized. Meanwhile, the isothermal transformation temperature of 550°C is at the upper limit specified in this application, and the reduced supercooling results in a slightly larger sorbite lamellar spacing. Therefore, the tensile strength of Example 2 (1783 MPa) and elongation after fracture (10.9%) are both slightly lower than those of Example 1.

[0070] In Example 3, the austenitizing temperature of 950℃ reached the grain coarsening temperature of 82B steel, resulting in the average grain size of the sorbite clusters after isothermal transformation coarsening from grade 7.5 in Example 1 to grade 6.0. However, the holding time in Example 3 was only 8s / 6s, shorter than the tens of seconds to several minutes of conventional furnace heating, effectively suppressing further grain coarsening. The isothermal transformation temperature of 450℃ is at the lower limit of this application, and the greater supercooling refined the interlamellar spacing of the sorbite, which improved the tensile strength of Example 3.

[0071] Example 4 distributed the deformation amount across 3+3+4 passes, with a lower single-pass compression ratio per segment compared to Example 1. The lower deformation amount means less work hardening of the wire after drawing, allowing for recrystallization under lower internal stress conditions during inter-segment sorbitization, resulting in more complete plastic recovery. Maintaining an average grain size of 7.5 demonstrates that increasing the number of sorbitization cycles did not lead to grain coarsening; this is attributed to the effect of short-term induction heating inhibiting grain growth. Example 4 exhibited the highest elongation after fracture among all methods.

[0072] Comparative Example 1 had an austenitizing temperature of 850°C. At this temperature, the proeutectoid cementite could not dissolve sufficiently, resulting in a carbon content in the austenite lower than the nominal carbon content of the steel and an uneven distribution. The average grain size of Comparative Example 1 was grade 8.0, finer than the 7.5 grade of Example 1. Although the sorbite clusters were fine, the properties were significantly degraded, with an elongation after fracture of 8.7%, 28 cycles of 360° torsion, and 20 cycles of 180° bending. This indicates that the fundamental problem with Comparative Example 1 was the inhomogeneous microstructure caused by insufficient austenitization, rather than the grain size.

[0073] Comparative Example 2 used the same salt bath immersion time as Example 1 (30 s), except that the isothermal transformation temperature was increased to 580°C. At 580°C, the supercooling was reduced by approximately 80°C compared to 500°C, resulting in a decrease in the pearlite nucleation driving force, a lower nucleation rate, and an increased interlamellar spacing. The transformation product deviated from the fine lamellar sorbite category and tended towards coarse pearlite. Comparative Example 2 exhibited a tensile strength of 1723 MPa, an elongation after fracture of 9.2%, withstanding 30 cycles of 360° torsion and 22 cycles of 180° bending. The decarburized layer depth was 0.012 mm, and the surface showed only slight scratches.

[0074] Comparative Example 3 employed 11 consecutive drawing passes, with all deformation accumulated during a single wire threading process. Due to the absence of inter-pass sorbitization treatment throughout the entire process, work hardening continuously accumulated within the 11 passes. The microcracks and localized necking tendency formed during deformation accumulation were irreversible, resulting in an elongation at break of 5.2%, significantly lower than the 12.6% of Example 1. The 360° torsion (27 passes) and 180° bending (17 passes) were also significantly lower than the 42 and 30 passes of Example 1, respectively. The absence of inter-pass base film recoating led to the gradual failure of the lubricating film in later passes, and the direct contact and friction between the wire and the die resulted in a rough surface. The number of passes required to achieve the same final diameter was two more than in Example 1, correspondingly increasing die consumption and production steps.

[0075] Comparative Example 4 retained the inter-segment sorbitization treatment, and its plasticity index was better than that of Comparative Examples 3 and 5, but not as good as that of Example 1. The difference stemmed from the lubrication method: Comparative Example 4 lacked a silane coupling agent base film, and the h-BN working film was only physically adsorbed onto the bare steel surface, making it easy to peel off under drawing shear force.

[0076] Comparative Example 5 eliminated the inter-segment sorbitization treatment but retained the inter-segment base film recoating and working film coating processes. Compared with Comparative Example 3, which also lacked inter-segment sorbitization treatment, Comparative Example 5 exhibited an elongation at break of 7.1%, significantly higher than Comparative Example 3's 5.2%; its visual appearance was also superior to Comparative Example 3. This indicates that the double-layer solid lubricating film reconstructed by inter-segment base film recoating effectively improves lubrication in terms of both elongation and surface quality.

[0077] Based on the comparative analysis of the above embodiments and comparative examples, it is further evident that the beneficial effects of this application are significant.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A multi-pass, low-deformation drawing process for preparing high-strength steel wire, characterized in that, It includes 2 to 3 drawing sections, each of which performs 3 to 4 consecutive drawing passes on the steel wire. The total compression rate of each drawing section does not exceed 55%, and the single-pass compression rate within each drawing section is 16 to 23%. The following steps are performed sequentially between two adjacent drawing sections: The steel wire is heated to 880-950℃ to austenitize it, and then isothermal transformation is carried out at 450-550℃ to transform the supercooled austenite into sorbite. Finally, it is cooled to below 200℃ under a protective atmosphere. After the steel wire has undergone sorbitizing treatment, a base film is recoated onto the surface, and then a working film is coated on the base film to form a uniform double-layer solid lubricating film. The working film is formed by coating with a nano-modified lubricant containing 1–3 wt% hexagonal boron nitride (h-BN) nanoparticles; the base film recoating includes: The surface of the cooled steel wire is steam-treated or sprayed with deionized water to regenerate hydroxyl groups on the surface of the steel wire. A dip coating solution is applied to the cooled steel wire surface, and then dried and cured at 120-150℃ for 30-60 seconds to form a nano pre-coating base film. The dip coating solution is prepared by a silane coupling agent and 1-3 wt% nano hexagonal boron nitride particles. The alkoxy group of the silane coupling agent is hydrolyzed to generate silanol (Si-OH), which undergoes a condensation reaction with the hydroxyl groups on the steel surface to form Si-O-Fe covalent bonds. At the same time, the intermolecular condensation of silane molecules forms a siloxane network, which anchors the h-BN nanoparticles in the network. Prior to the first drawing section, the following also applies: The wire rod is dip-coated with the aforementioned dip-coating solution, and then dried and cured at 120–150°C for 60–90 seconds to form a nano-pre-coated base film on the surface of the wire rod.

2. The process according to claim 1, characterized in that, In the multi-pass drawing process, the cone angle of the compression zone of the drawing die gradually decreases from the inlet end to the outlet end.

3. The process according to claim 2, characterized in that, The inlet cone angle of the compression zone of the drawing die is 12-15°, and the outlet cone angle of the compression zone is 6-8°.

4. The process according to claim 1, characterized in that, The isothermal transformation is a salt bath isothermal transformation; the salt bath isothermal transformation includes: The austenitized steel wire is immersed in a molten salt bath containing nitrates at a temperature of 450–550°C for 10–60 seconds.

5. The process according to claim 1, characterized in that, The protective atmosphere is nitrogen or a mixture of nitrogen and propane.

Citation Information

Patent Citations

  • Drawing process of high-carbon steel filament

    CN113680840A

  • Manufacturing method of carbon steel wire with diameter of 0.05 mm

    CN109940054A

  • Wire rod, preparation method of wire rod, mining 2400MPa-grade steel strand and manufacturing method and application of mining 2400MPa-grade steel strand

    CN119753505A

  • Drawing method for improving surface quality of high-temperature alloy bar

    CN121082707A

  • Multi-pass wire rod rough drawing lubricating and cooling integrated process

    CN122252475A